Considering Matthew Shepard: normative and anti-normative queer spatial narratives and the politics of performance in choral music. (October 2019) - Cockayne, Daniel
I present a cultural geographical analysis of the recent choral composition Considering Matthew Shepard . I explore the cultural, musical, and emotional geographies of this piece of music, in terms of its content and my experience of rehearsing and then performing the piece as a member of the choir. Drawing on cultural geography, musical geography, and queer theory, I argue that the memorializing of Matthew Shepard's killing through this musical setting both repeats and challenges the normative popular and academic framings of Shepard's murder and, more generally, queer critiques of the memorialization and historicization of lesbian, gay, bisexual, transgender, and queer pasts. I explore this by examining three spatial themes in Considering Matthew Shepard : its representations of (1) Wyoming, (2) the fence (where Shepard was left by his assailants), and (3) universality. I also point to what musical geographies might gain in looking more closely at choral music performance.